The eight inter-Asian corn improvement workshop (Department of Agriculture, 1972)
This workshop includes special presentations about physiological aspects of grian yield of maize; Effect of different plant populations and combinations of N P K on the Gian Yeild of improved maize under late sown condition in the Kathhmandu Valeey, Nepal;...